ID: 156. Issue 1 (November 2015) - Diefenbach, Andreas
<x xml:space="preserve">Abstract</x> Innate lymphoid cells (ILCs) are a recently discovered family of innate lymphocytes that are substantially represented at mucosal surfaces and have been implicated in the protection of epithelial barriers. Various types of ILCs can be discriminated based on the expression of distinct transcription factors controlling the expression of a distinct set of cytokine genes endowing the various ILC subsets with a specific range of effector functions. Currently, three groups of ILCs are being recognized. Group 1 ILCs (ILC1s) are a diverse group of ILCs comprised of natural killer (NK) cells and other, poorly defined subsets of ILCs. It is believed that the ILC1 fate decision is controlled by the T-box transcription factor T-bet endowing ILC1s with the capability to produce large amounts of IFN-γ. ILC2s express high levels of GATA-3, produce IL-5 and IL-13 and have been involved in immunity to helminth infections and in the pathogenesis of allergic diseases. Group 3 ILCs developmentally depend on the transcription factor RORγt and produce the cytokines IL-22, IL-17A and IL-17F. ILC3s are believed to be involved in the protection against intestinal bacterial infections and, if inappropriately stimulated, can be important drivers of inflammatory disorders. The transcriptional programs and effector cytokines of the various ILC subsets strikingly resemble those of the various T helper cell effector fates suggesting that such transcriptional circuitry already formed in the evolutionary older innate immune system. The various ILC subsets are developmentally related as all ILC lineages depend on the transcriptional regulator Id2 (inhibitor of DNA binding 2) that interfers with E2 protein-controlled gene expression. This raises the important issue if ILCs may derive from a common ILC progenitor (CILP). Identification of such a progenitor would allow to identify the molecular signals required for the specification of the various ILC lineages. I will discuss progress towards our understanding of the molecular programs regulating ILC fate decisions and our current models of transcriptional stability and plasticity of ILC fates. Finally, I will discuss an unprecedented role of ILC3s in the protection against mucosal virus infections. Research in my lab is supported by grants from the European Research Council (ERC) and Deutsche Forschungsgemeinschaft.